Awareness and understanding among students on sustainable campus at Universiti Teknologi Malaysia (UTM) - Chong, Yan Yee, 1996-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2020